2014
DOI: 10.3109/01612840.2014.924608
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate Education in Psychiatric Nursing in Israel: Closing the Gap

Abstract: Deinstitutionalization policies are being gradually implemented in Israel. Most recently, an insurance reform has been approved, in which mental health services will be included in the HMO's service package. As most Israeli mental health nurses are currently employed in institutional settings, the Ministry of Health's Nursing Division seeks to estimate their scope of employment in preparation for the anticipated changes. The aim of this study is to describe present-day professional practice characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As evident in the literature, it is very likely that mental health nurses whose training emphasized psychosocial model of care would be better able to meet these complex needs. Since the psychosocial model emphasizes holistic care, a well-developed multidisciplinary mental health team will be better able to offer multidimensional perspectives and as such should be the basic platform for delivering mental health care (Haron et al, 2014;Mental Health Commission, 2006;Sheer & Wong, 2008). The current mental health training for nurses in Malaysia, is basically traditional, primarily doctor led, bureaucratic, using the biomedical-custodial model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As evident in the literature, it is very likely that mental health nurses whose training emphasized psychosocial model of care would be better able to meet these complex needs. Since the psychosocial model emphasizes holistic care, a well-developed multidisciplinary mental health team will be better able to offer multidimensional perspectives and as such should be the basic platform for delivering mental health care (Haron et al, 2014;Mental Health Commission, 2006;Sheer & Wong, 2008). The current mental health training for nurses in Malaysia, is basically traditional, primarily doctor led, bureaucratic, using the biomedical-custodial model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from different countries have highlighted this problem of inadequate training for nurses working with the mentally ill. This literature shows that there is a severe shortfall in the number of trained mental health nurses in inpatient and community settings (Haron, Gun-Ushishkin, Shor, Tran, & Riba, 2014; National Confidential Inquiry into Suicide and Homicide by People with Mental Illness [NCISH], 2015;Stuhlmiller, 2005). Agar et al (2012) reported that nurses lack the knowledge and capabilities to effectively assess and manage mental illness in acute settings.…”
Section: Introductionmentioning
confidence: 99%
“…A countrywide sample of nurses with post-basic training in State psychiatric hospitals identified areas of practice for further training: psychotherapy intervention (60% of respondents); consultation for the elderly (60%); care prescriptions (64%); community drug-treatment management (69%), and referral to professionals and community resources (56%). Nurses reported gaps in the continuity of care and community rehabilitation activities [20]. These findings have implications for training in an era of greater focus on chronic mental illness in the community.…”
Section: Health Systems and Policy Research Issn 2254-9137mentioning
confidence: 94%